Transitional two-phase flow around 90° bends of different orientations - Omar, Rajab Abulgasem (2017)
Considering the gap in available information and the need of the industries such as oil and gas production, energy, and food processing, this study focuses on the two phase flows around bends in process pipe lines. The aim of this study is to investigate the influence of 90° bends on the gas-liquid two phase flow behaviour in vertical and horizontal orientations using advanced two-phase flow measuring techniques. An experimental study has been conducted using silicone oil with a viscosity of 5 mPa.s and air to examine the transitional flows around 90° bends of 68 mm internal diameter (ID) with different configurations. Experiments were conducted at ambient conditions in an open system which consists of a 68 mm ID riser of 4.5 m long, vertical upward 90° bend and two horizontal sections of a 9.2m and 5.5m long in series with a horizontal 90° bend in between. The experimental matrix comprises 60 combinations of gas and liquid superficial velocities, ranging from 0.045 m.s-1 to 3.21 m.s-1 and 0.15 m.s-1 to 0.53 m.s-1 respectively. The phase distributions within the pipes were measured using Electrical Capacitance Tomography (ECT) and Wire Mesh Sensors (WMS). The behaviour of the flow was examined qualitatively using high speed imaging. To study the flow development in the riser, both ECT and WMS were placed in series and moved along three axial locations downstream of the mixing section. During the experiments at the bends, the ECT was kept immediately upstream while the WMS was moved to different positions downstream of the bend. The cross-sectional void fraction time series from the ECT and the WMS were used to quantify the main hydrodynamic parameters of the flow including cross-sectional averaged void fraction, bubble size distribution, radial void fraction profiles, slug length, slug frequency, void fraction in liquid slugs, and the slug bubble velocity. Results were compared against the available slug flow correlations. The results show that the phases separate shortly after the vertical to horizontal bend leading to stratified or wavy stratified flow. Beyond a certain threshold of the gas flow rate and liquid level, onset of slugs can be observed at a certain distance downstream of the vertical upward bend. This work suggests that the formation of hydrodynamic slugs downstream of the vertical upward bend is independent of the inlet conditions upstream. The horizontal bend, unlike the vertical upward bend, has a minor influence on the flow evolution, particularly slug flow. This is due to the influence of gravitational force on phase separation and its subsequent effect on the change of momentum in the vertical bend. The flow structures, mainly slugs and disturbance waves, are slightly accelerated as they pass through the horizontal bend with minimum change to the structure frequency and gas holdup within liquid slugs. Most of the existing correlations do not predict the measured void fractions in this work as those correlations were essentially limited to the conditions they were developed for as the basis of them lies in the curve fitting. In this work, the higher viscosity and lower surface tension led to higher gas holdup in liquid slugs causing the discrepancy.